A scientific-philosophical vocation? Education, the construction of the intellectual field, and the routinization of the sacred as a way of structuring Umbanda from the 1940s onwards. (Ágora Journal, 2026)
This paper analyzes how different federative projects attempted throughout the 20th century to elevate Umbanda to the category of religion through the analysis of the Umbanda religious field. As sources, we used newspaper articles related to the history of Umbanda and the Proceedings of the First Brazilian Congress of Umbanda Spiritism. Finally, we intend to demonstrate, based on Ortiz (1991) and Camargo (1961), how education was a fundamental value for the different segments of Umbanda, which can be proven by the founding of Umbanda publishing houses and the vast publication of Umbanda books in the second half of the 20th century.
Keywords: Umbanda; Coding; Education.